Mitigation of platinum depletion in platinum diffused single phase bond coat on CMSX-4 superalloy - Bai, Mingwen; Chen, Ying; Sun, Yongle; Xiao, Ping (MDPI, 2021)
Pt-diffused bond coat with a mixture of γ/γ’ phase has just been developed in the recent decades as a cheaper alternative to the Pt-enriched β-phase Aluminide bond coat that contains a higher content of Al. However, concerns are raised on the inevitable depletion of Pt near the coating interface that may endanger the component after long-term service. In this study, modified Pt-diffused bond coats with a single phase (γ or γ’) were made by applying selective etching on CMSX-4 single crystal superalloys prior to the electroplating of Pt. The single-phase bond coats show distinctive diffusion behaviour in comparison with the conventional γ/γ’ bond coat. Surprisingly, Pt remains more stable in the γ’-phase bond coat with significantly less depletion after diffusion, which implies a potential in saving a considerable amount of Pt. On the other hand, however, the depletion of Pt is more severe in the γ-phase bond coat. The mechanism that governs the diffusion behavior of Pt in the γ and γ’-phase was also discussed that mainly concerns with thermodynamic and kinetic factors.
Keywords: bond coat; platinum; diffusion; thermodynamic; thermal barrier coatings